57. Portable Applications in Mobile Education - Baggaley, Jon (International Review of Research in Open and Distributed Learning, 2006)
Portable software applications can be carried on a convenient storage medium such as a USB drive, and offer numerous benefits to mobile teachers and learner. The article illustrates the growing field of ‘portable apps’ in reviews of seven contrasting products. These represent the major categories of document editing, email maintenance, Internet browsing, instant messaging, file transfer, multimedia presentation, and anti-virus protection. Emphasis is placed on ways to use ‘portable apps’ to overcome the common problems of Internet usage during travel.